A proposed theoretical model of help‐seeking among Korean‐American women with urinary incontinence12. Issue 2 (1st October 2012) - Kang, Youngmi
ABSTRACT There is no integrated theoretical model explaining help‐seeking for urinary incontinence (UI) that links individual factors to socio‐cultural and systemic factors among Korean‐American women. The purpose of this article was to develop a theoretical model derived from a systemic perspective to explain the help‐seeking among Korean‐American women with UI. The Behavioural Model for Vulnerable Populations derived from a systemic perspective was adapted to develop a theoretical model. Individual factors (i.e. biological risk factors, health beliefs, social structure, income, a regular source of health care and perceived need), systemic factors (i.e. social support and transportation), and unique cultural factors (i.e. acculturation, family tradition and authority, and the preference of a health care provider) were included in the theoretical model. A proposed theoretical model in this article will give an opportunity to understand the relationships among factors that influence to help‐seeking among Korean‐American women with UI. This will be helpful to design culturally competent UI care intervention for Korean‐American women.